The global network antenatal corticosteroids trial: impact on stillbirth. Issue 1 (December 2016) - Goldenberg, Robert; Thorsten, Vanessa; Althabe, Fernando; Saleem, Sarah; Garces, Ana; Carlo, Waldemar; Pasha, Omrana; Chomba, Elwyn; Goudar, Shivaprasad; Esamai, Fabian; Krebs, Nancy; Derman, Richard; et al.
Abstract Background Antenatal corticosteroids are commonly used to reduce neonatal mortality, but most research to date has been in high-resource settings and few studies have evaluated its impact on stillbirth. In the Antenatal Corticosteroids Trial (ACT), a multi-country trial to assess impact of a multi-faceted intervention including antenatal corticosteroids to reduce neonatal mortality associated with preterm birth, we found an overall increase in 28-day neonatal mortality and stillbirth associated with the intervention. Methods The ACT was a cluster-randomized trial conducted in 102 clusters across 7 research sites in 6 countries (India [2 sites], Pakistan, Zambia, Kenya, Guatemala and Argentina), comparing an intervention to train birth attendants at all levels of the health system to identify women at risk of preterm birth, administer corticosteroids and refer women at risk. Because of inadequate gestational age dating, the <5th percentile birth weight was used as a proxy for preterm birth. A pre-specified secondary outcome of the trial was stillbirth. Results After adjusting for the pre-trial imbalance in stillbirth rates, the ACT intervention was associated with a non-significant increased risk of stillbirth (aRR 1.08, 95 % CI, 0.99–1.17, p –0.073). Additionally, the stillbirth rate was higher in the term births (1.20 95 % CI 1.06–1.37, 0.004) and among those with signs of maceration (RR 1.18 (1.04–1.35), p = 0.013) in the intervention vs. control clusters. Differences in obstetric care favored the control clusters and maternal infection was likely more common in the intervention clusters. Conclusions In this pragmatic trial, limited data were available to identify the causes of the increase in stillbirths in the intervention clusters. A higher rate of stillbirth in the intervention clusters prior to the trial, differences in obstetric care and an increase in maternal infection are potential explanations for the observed increase in stillbirths in the intervention clusters during the trial. Trial registration clinicaltrials.gov (NCT01084096)